Forming A Culture of Environmental Safety in Primary School Students - Donaeva Shakhnoza (Research Parks Publishers, 2021)
The article describes the formation of a culture of environmental safety in primary school students, a creative approach to environmental culture, its content, form and methods, theoretical, practical and educational problems of environmental safety, environmental destruction or environmental situation, as well as its teaching infrastructure.